Long-term hybrid galvanic corrosion protection of reinforced-concrete structures. Issue 4 (18th August 2022) - Christodoulou, Christian; Dodds, Wayne; Goodier, Chris; Stone, Christian
Abstract : Hybrid corrosion protection (HCP) can be used to provide corrosion arrest and prevention in degrading reinforced-concrete structures to increase their service life. The proprietary technology is a relatively new electrochemical treatment for concrete structures, having been patented in 2005 (patent GB2426008B). Due to this fact, accurate and reliable empirical data over the life span of a structure protected by an HCP system does not yet exist. This paper is the first to present over 10 years of empirical data, from one of the very first installations of HCP, providing a rigorous and reliable assessment of the structure's long-term performance. Results demonstrate that hybrid galvanic anodes exhibit a responsive behaviour to maintain the concrete environment and respond to corrosion hazards. Even after prolonged periods of low current output, the anodes respond to changing environmental conditions, providing the higher current output required to afford the necessary polarisation to the reinforcement, and hence the protection to the structure. Steel potentials also continued to trend towards more positive values, a generally agreed indication of passive reinforcement. Overall, this study is unique, being the first to present continuous, long-term performance data on hybrid galvanic anodes for the corrosion protection of reinforced-concrete structures.